Development of Sports Psychology Research and Athlete Performance in Reputable International Journals: Bibliometric Analysis - Putu citra Permana Dewi; Yasep Setiakarnawijaya; Kadek Dian Vanagosi; Lusiana; S.M. Fernanda Iragraha (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
This study aims to be able to map the scope of sports psychology research on the Scopus scientific article database. The research focus to describe the thematic areas that most attract the attention of academics, to analyze the development of research on sports psychology which is associated with athlete performance. This research method is descriptive quantitative with a bibliometric approach, assisted by Publish or Perish and VosViewers software. Research sample from the last two decades (2002-2022). Through the keywords